Investigation of Pre-service Primary School Teachers' Decision Processes Related to Genetic-based Socioscientific Discussions in Terms of Human Rights - Ayşe Öztürk; Ahmet Doğanay (Sakarya University Journal of Education)
In this study, it was aimed to investigate the decision processes ofpre-service primary school teachers (PPSTs) related to genetic-basedsocioscientific discussions in terms of human rights. In this context, in thestudy, it was focused on the birth of gifted people with genetic technology,the use of genetic tests in the process of getting health insurance, and genderselection by the PGD method. The study was carried out as a descriptive studyin the screening model with 203 PPSTs studying at the fourth grade in threefaculties of education in the Southeastern Anatolia region in Turkey. In thestudy, the data were collected with the Evaluation Form for Decision Processesrelated to Genetic-based Socioscientific Discussions. Research data wereanalyzed by content analysis. The results of the study indicated that PPSTsused different decision processes in genetic-based socioscientific discussionsand based these decision processes on different justifications. Furthermore,they also revealed that PPSTs largely made decisions that were unrelated tohuman rights in genetic-based socioscientific discussions. However, they couldusually make accurate inferences when they made human rights-based decisions.This study is important in terms of providing information on how PPSTs'decision processes related to genetic-based socioscientific discussions areshaped and on how human rights are employed in this process.